Strategi Kepala Sekolah Dalam Mengelola Sarana Dan Prasarana Di MTs Darunnajah Cipining - Arizqi Ihsan Pratama Arizqi; Vira Zahirah; Taufiq Nur Azis; Nur Rochmat (CV. ALIM'SPUBLISHING, 2023)
Educational facilities and infrastructure are facilities used for the implementation of educational activities so that the infrastructure used to support the learning process can still function properly. Therefore, school principals need to have a strategy in managing facilities and infrastructure so that they can still be used to support the occurrence of a quality learning process. The study used a qualitative descriptive method. The research subjects were school principals, vice principals in the field of facilities and infrastructure, teachers, and students. Collecting data by interview, observation, and recording. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results showed that: (1) the management of facilities and infrastructure at MTs Darunnajah 2 Cipining went well, this was due to several strategies developed by the principal in the management component of facilities and infrastructure. (2) To realize some of these strategies, the principal needs to take steps to implement the principal's strategy, and in this case the principal includes several teachers/staff/employees as the person in charge of each facility and infrastructure.